KAJIAN DAMPAK LINGKUNGAN SOSIAL DAN EKONOMI AKIBAT KEGIATAN PENAMBANGAN BAHAN GALIAN GOLONGAN C DI DAERAH KAWASAN PESISIR SAOKA SORONG BARAT - Rahmatullah, Azwar; Budianto, Agus; Abubakar, Endang (Universitas Ahmad Dahlan, 2024)
Background: The declining quality of seawater has an impact on the social and economic sectors of the community, whose livelihoods actually rely on the coastal areas. It starts with the decline in the tourism sector and the catchment area of fishermen, who have to go farther to catch fish. This study aims to determine the impact of Disposal C waste distribution on the surrounding environment and investigate the quality of seawater polluted by waste disposal from Class C quarrying activities. It also determined the socioeconomic aspects of the mining community. Method: The research methods consisted of water quality analysis, questionnaire distribution, and analytical hierarchy processing. Result: The results indicated that infall TSS was 21 mg/l and outfall TSS was 18 mg/l. Infall turbidity was 11.9 NTU and outfall turbidity was 0 NTU. Infall BOD was 2.28 ml/l and outfall BOD was 1.92 ml/l. The total infall coliform was 9200 MPN/100 ml and the outfall coliform was 45 MPN/100 ml. There were four social impacts and four economic impacts. The environmental impact showed a change of 11.50% or 8.362 m2, and the total exploration area had 72.687 m2.